Alternatives to automated people‐mover systems for small but dense populated areas - Scherer, Milena; Wichser, Jost; Venckauskaitė, Jūratė (Technological and Economic Development of Economy, 2009)
This paper describes the operational and technical requirements for a high quality public transport system in the country of Liechtenstein and is based on a study conducted by the Institute for Transport Planning and Systems (IVT) at the ETH Zurich. In this case study, a new public transport system (NPT) is defined as a new guideway transport system introduced in a region where this system does not exist yet. Often there are forms of a new technology, for instance, an automated people mover or a modern tramway. Some of the surveyed NPTs are not introduced in many places. The Liechtenstein case study made it possible to analyze, why these systems have not been successful than expected and what is the most appropriate way to introduce a NPT in this country.Automatizuoto transporto mažose bei tankiai apgyvendintose teritorijose alternatyvosSantrauka. Aprašomas poreikis sukurti aukštos kokybes viešojo transporto sistemą Lichtenšteino kunigaikštystėje. Remiamasi Ciuricho planavimo ir transporto sistemų instituto parengta studija. Šiame tiriamajame darbe pasiūlyta nauja viešojo transporto sistema. Dažnai naujos technologijos sistemos suprantamos kaip automatizuotas transportas, pvz., modernus tramvajus. Lichtenšteino studija parode, kodėl ne visos naujos transporto sistemos sėkmingos, kaip tikimasi. Studijoje pasiūlytas priimtiniausias naujos Lichtenšteino viešojo transporto sistemos būdas.Reikšminiai žodžiai: nauja viešojo transporto sistema, Lichtenšteino studijos tiriamasis darbas, auganti ekonomika, didėjanti transporto paklausa, tarptautine transporto paklausa, migracija.First published online: 21 Oct 2010